C-S-H seeding activation of Portland and Belite cements: An enlightening in situ synchrotron powder diffraction study. (November 2022) - Morales-Cantero, Alejandro; Cuesta, Ana; De la Torre, Angeles G.; Santacruz, Isabel; Mazanec, Oliver; Borralleras, Pere; Weldert, Kai Steffen; Gastaldi, Daniela; Canonico, Fulvio; Aranda, Miguel A.G.
Abstract: C-S-H seeding in Portland cements is well known from basic scientific works and field applications. Moreover, this activation approach could be beneficial for low-CO2 cements under development where a general drawback is poor mechanical strengths during the first week of hydration. However, a mechanistic understanding of the different processes taking place when seeding is still not developed. Here, we contribute to this knowledge gap by studying one commercial Portland cement and two industrial-trial belite cements. Three different admixtures are employed, viz. two types of commercial C-S-H seeding and triisopropanolamine as a typical alkanolamine. A multitechnique approach is employed including calorimetry, ultrasonic pulse velocity, thermal analysis and Rietveld analysis of laboratory X-ray powder diffraction data. Chiefly, an in situ X-ray synchrotron diffraction study has allowed mapping out the evolution of every crystalline phase. Furthermore, the use of an internal standard permitted to measure the changes in the overall amorphous content. In a nutshell, alite and belite (phases) hydrations are not significantly accelerated by C-S-H seeding for the three studied cements. Conversely, sulphate and aluminate phase dissolutions are enhanced. Faster ettringite crystallisation contributes to the observed improved mechanical properties at early ages. Moreover, a synergistic effect between C-S-H seeding and alkanolamine addition is proved. The importance of these findings for the possible acceleration of low-CO2 cement hydration is discussed.